Switzerland 2026 - Williams, Nicola, 1971-; Bishop, Caroline (Caroline Helen); Di Duca, Marc; Haywood, Anthony; Richmond, Simon; Walker, Kerry (Travel writer) (Lonely Planet guidebooks., 2026)
Lonely Planet's local travel experts reveal all you need to know to plan the trip of a lifetime in this latest edition of our guide to Switzerland. Discover Switzerland's most popular experiences and best kept secrets from following in Mark Twain's footsteps up Mt Rigi for panoramic views; to admiring masterpieces by Picasso, Klee and other modern masters at Sammlung Rosengart; and hiking through vineyards with music, winegrowers and tasting glass in hand in Sierre.